OPTIMISING ENDODONTIC DISINFECTION: SEM EVALUATION OF APICAL PREPARATION SIZES COMBINED WITH PHOTODYNAMIC THERAPY IN APICAL THIRD OF MANDIBULAR FIRST MOLARS - Hammad, Hina; Irfan, Fariha; Shah, Haroon; Rehman, Abdur; Kumar, Chander; Hammad, Muhammad; Ali, Syed Abrar (Journal of Ayub Medical College Abbottabad, 2024)
Background: Eliminating microorganisms from the root canal system is crucial for successful treatment. Rotary nickel-titanium systems have revolutionized endodontics, but their ability to reduce microbial counts within dentinal tubules remains under-researched. Proper apical size selection is crucial for cleaning without compromising radicular dentine. Removal of smear layer is crucial as it obstructs disinfectant penetration. To enhance traditional irrigation, photodynamic therapy utilizing photosensitizers and lasers, presents a novel antimicrobial approach. This research aims to explore the correlation between different final apical preparation sizes combined with photodynamic therapy in smear layer removal, utilizing SEM on extracted molars. Methods: Forty-two decontaminated human mandibular first molars were divided into four groups based on different apical size preparations. All groups were prepared with different apical preparation sizes. All groups underwent photo-activated disinfection along with standard irrigation. A diode laser, combined with a photosensitizer, was used for smear layer removal, followed by SEM assessment. SEM images were evaluated for smear layer removal in the apical third using established criteria. Data analysis employed One Way Anova. Results: Group 3 proved most effective in smear layer removal, while group 1 was the least effective. Both group 1 and group 2 showed similar, minimal removal rates. The control group had a significant presence of smear layer. Statistical analysis revealed significant differences in smear layer removal efficacy across the groups, with a p-value <0.05. Conclusion: Photodynamic therapy effectively removes smear layer in apical third of the root when sufficiently prepared, serving as a valuable adjunct to conventional regimen.